PENGGUNAAN PINJAM NAMA PERSEROAN TERBATAS DALAM PERSPEKTIF HUKUM PAJAK DAN PENGARUHNYA TERHADAP PENERIMAAN PAJAK - Kusumastutia, Anindita Sari; Khalimi, Khalimi; Tondy, Cicilia (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
The practice of using nominees in business and tax relationships has a significant legal impact, both in terms of legal certainty, accountability, and state revenue. This study examines the legal impact of name borrowing practices on companies as outlined in Decision No. 29 / Rev.G/2022 / PN.Mdn. This case involves the use of the name PT Guna Karya Nusantara by substantive parties to meet the requirements of the tender, which resulted in tax problems due to unknown tax arrears. The study also discusses the weak regulation that allows tax evasion through nominee practices and the ineffectiveness of tax collection in the current Indonesian tax system. From the perspective of legal theory, this study uses Gustav Radbruch's principle of legal certainty and Milton Friedman's theory of accountability to assess emerging legal problems. The results of the analysis show that the non-transparent legal relationship between formal and substantive parties creates legal loopholes that can be exploited, thereby weakening the self-assessment based taxation system. In addition, the direct impact of this practice is significant state losses due to delayed tax revenues. As a solution, the Directorate General of taxes designed the reform of the tax system through the implementation of the Core Tax Administration System (CTAS) in 2025. The system replaces the central and branch taxpayer mechanisms with a single entity, thereby strengthening transparency, accountability, and efficiency in tax enforcement. This study recommends revisions to regulations, including the KUP law and Presidential Regulation No. 12 of 2021, in order to eliminate legal loopholes related to nominees, as well as provide strict sanctions to violators. With a holistic approach, this study concludes that reforming the tax system and strengthening regulation is needed to prevent tax evasion and ensure the fairness and effectiveness of the law in supporting state revenue